PENGARUH LITERASI KEUANGAN, AKSES PERMODALAN, FINTECH PEER TO PEER LENDING DAN PAYMENT GATEWAY TERHADAP KINERJA KEUANGAN UMKM DI KECAMATAN MATARAM - DIANITA ANNISA PUTRI; NI NYOMAN YULIATI; RUSLI AMRUL (Universitas Mahasaraswati K. Mataram, 2024)
This study aims to examine the influence of financial literacy, access to capital, fintech peer to peer lending, and payment gateways on the financial performance of MSMEs. This study uses a quantitative method with an associative approach. The population in this study is all MSMEs in Mataram District. The sample was taken using the purposive sampling method with the criteria of MSME actors in Mataram District, MSME actors registered with the Mataram City Cooperatives & SMEs Office, MSME actors who are Small and Medium Enterprises, and MSME actors who use Payment Gateways so that a sample of 100 MSMEs was obtained. Data was obtained by distributing 100 questionnaires to MSME actors in Mataram District directly and through google forms. The analysis data used SPSS 27 with classical assumption test and multiple linear regression. The results of this study show that independent variables (financial literacy, access to capital, fintech peer to peer lending, and payment gateway) are able to influence the dependent variable (MSME financial performance) by 68.2% while the remaining 31.8% of MSME financial performance is influenced by other variables outside the regression model used in this study.